A compact uniform circular array antenna for circularly polarized higher-order OAM beam generation through modes superposition - Fayyaz, Umar; Aladadi, Yosef T.; Aziz, Abdul; Niazi, Shahab Ahmad; Shah, Syed Tamoor; Al-Sowayan, Sulaiman; Shamsan, Zaid Ahmed; Hussain, Rifaqat (PLOS ONE, 2026)
This paper presents the design and validation of a compact uniform circular array (UCA) antenna for the generation of a higher-order orbital angular momentum (OAM) beam. The array combines the fifth-order OAM generated by individual ring patch antenna elements with the first-order OAM mode of the array to radiate the resultant sixth-order OAM beam through mode superposition. A dual-feed configuration is employed to achieve a 90-degree phase difference using differential feed lengths. Sequential rotation of elements ensures circular polarization without the need for complex feeding networks. Characteristic Mode Analysis (CMA) confirms the excitation of TM61 degenerate modes from ring patch antenna responsible for the fifth-order OAM radiation. The antenna operates at 3.55 GHz and achieves significant mode purity with an axial ratio below 3 dB. The proposed design is a single-layer, low-profile antenna that is suitable for narrowband OAM-based wireless sensor and communication systems, enabling high-order mode generation with a reduced number of array elements.